Shakespeare: transformações em imagens - Vollmer Filho, Germano; Duarte, Aldo Luiz Coelho Borges; Bugin, Alice Milman; Lahude, Denise Vivian; Maltz, Flávia Friedman; Vollmer, Guilherme Galant; Fortes, Suzana Deppermann (Revista de Psicanálise da SPPA, 2013)
No presente trabalho os autores procuram compreender a atividade criativa de Shakespeare à luz da teoria das transformações, de Bion. Atribuem a criatividade e atualidade da obra do poeta e dramaturgo às transformações de emoções e sensações humanas em imagens, representadas por seus personagens, que enfrentam as questões da vida e da morte. Buscando as raízes desta capacidade, creem ser a principal delas o fato de, cedo na vida, ter-se defrontado com a morte devido à peste que assolou a Europa e com a vida graças ao amor extremo de sua mãe. Algumas passagens da obra de Shakespeare são citadas para ilustrar os pontos de vista dos autores. Shakespeare: transformations into images In this paper the authors try to understand Shakespeare’s creative activity utilizing Bion’s transformation theory. They attribute the creativity and current content of the work poet and playwright’s to the transformations of human emotions and sensations into images, represented by his characters, which face the issues of life and death. Searching the roots of such capacity, they believe that the main fact was that, early in life, Shakespeare was confronted with death due to the pest which devastated Europe, and with life due to the extreme love from his mother. Some passages of Shakespeare’s work are mentioned to illustrate the authors’ vantage points.